A sodium ion battery positive electrode material with gradient structure and its preparation method and application

By designing a core-shell structure with a gradient structure in the positive electrode material of sodium ion battery, the problems of poor stability and harsh environment of existing materials at high voltages are solved, and the improvement of high-pressure stability and air stability is achieved, as well as in high humidity environments Excellent storage performance under

CN118676349BActive Publication Date: 2025-02-11GUIZHOU ZHENHUA E CHEM INC +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411083223.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2025-02-11
Estimated Expiration
2044-08-08

AI Technical Summary

Technical Problem

Existing sodium-ion battery layered oxide positive electrode materials are prone to excessive desodiumization at high voltages, causing transition metal layer slippage, affecting electrochemical performance, and demanding environmental requirements during storage and transportation, resulting in high costs.

Method used

Using a core-shell structure positive electrode material with a gradient structure, the core and cladding layer have specific chemical composition and structure, the sodium concentration increases from the outer surface to the inner gradient, and the manganese concentration decreases from the outer surface to the inner gradient, and the core and The composition ratio of the cladding layer improves the high-pressure stability and air stability of the material.

Benefits of technology

It effectively improves the high-pressure stability and air stability of the material, ensures the charge and discharge capacity and circulation stability, and also shows excellent storage performance in high humidity environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118676349B_ABST
    Figure CN118676349B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of sodium ion battery positive electrode materials, and specifically relates to a sodium ion battery positive electrode material with a gradient structure and a preparation method and application thereof. The sodium ion battery positive electrode material is a core-shell structure, which includes a core and a coating layer. The positive electrode material has a composition shown in formula I: Na e Ni a Mn b Fe c M d O2, wherein 0.8≤e≤1.05, 0.2≤a≤0.35, 0.2≤b≤0.5, 0.15≤c≤0.4, and 0.01≤d≤0.16. M is selected from one or more of Ti, Mg, Zn, Li, Al, B, Cu, Cr, Zr, Y, Ce, La, Sm, Se, Sr, Nb, W, Ta, and V; the sodium content increases from the outer surface to the inner part, and the manganese content decreases from the outer surface to the inner part. The present invention regulates the gradient structure of the sodium concentration and the manganese concentration in the composite material, and its special structure further effectively improves the high-voltage stability and air stability of the positive electrode material of the sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery positive electrode material with a gradient structure, a preparation method and an application thereof. Background Art

[0002] Currently, lithium-ion batteries are widely used in mobile electronic devices, new energy vehicles and energy storage, but lithium resources are scarce, unevenly distributed and difficult to mine. As lithium-ion batteries become popular, lithium ore prices continue to rise, and the cost of lithium-ion batteries continues to rise. Sodium resources are widely distributed and cheap, and sodium-ion batteries have similar working principles to lithium-ion batteries, and are receiving more and more attention. Among the positive electrode materials of sodium-ion batteries, layered oxide materials are expected to become a type of material that can quickly realize the industrialization and commercial application of sodium ions due to their high energy density, wide selection of raw materials, and the ability to use existing lithium-ion battery positive electrode material preparation processes.

[0003] The crystal structure of layered oxide materials is composed of repeated stacking of alkali metal layers and transition metal layers. During use, sodium ions repeatedly escape / embed into the alkali metal layers to realize the charge and discharge process. Improving the charge and discharge voltage of layered positive electrode materials can increase the charge and discharge capacity of positive electrode materials. However, under high voltage, the transition metal layer of layered oxide positive electrode materials undergoes irreversible slip due to excessive sodium removal, which hinders the reversible escape / embedding of sodium ions in the transition metal layer, seriously affecting the electrochemical performance of layered oxides. At the same time, when the sodium ion positive electrode material is in a relatively humid environment, water and carbon dioxide molecules are easily intercalated with the layered oxide, generating inert substances such as sodium carbonate in the transition metal layer, and destroying the layered structure of the positive electrode material, seriously affecting the storage and transportation of the material. Therefore, it is an urgent problem to develop a sodium ion battery positive electrode material with high specific capacity, excellent rate performance, cycle stability and air stability. Summary of the invention

[0004] Technical problem solved by the present invention: In the prior art, sodium ion battery layered oxide positive electrode materials are prone to excessive sodium removal under high voltage, thereby causing transition metal layer slip, seriously affecting the electrochemical properties of the layered oxide; moreover, sodium ion positive electrode materials have relatively stringent requirements on the environment during storage and transportation, and the storage and transportation costs are relatively high.

[0005] In response to the above technical problems, the present invention provides a sodium ion battery positive electrode material with a gradient structure composite phase and a preparation method and application thereof.

[0006] Specifically, the present invention provides the following technical solutions:

[0007] In a first aspect, the present invention provides a positive electrode material with a gradient structure, wherein the positive electrode material is a core-shell structure, comprising a core and a coating layer, wherein the coating layer is coated on the outer surface of the core; the positive electrode material has a composition shown in Formula I: Na e Ni a Mn b Fe c M d O2, wherein 0.8 ≤ e ≤ 1.05, 0.2 ≤ a ≤ 0.35, 0.2 ≤ b ≤ 0.5, 0.15 ≤ c ≤ 0.4, 0.01 ≤ d ≤ 0.16, M is selected from one or more of Ti, Mg, Zn, Li, Al, B, Cu, Cr, Zr, Y, Ce, La, Sm, Se, Sr, Nb, W, Ta and V; the concentration of sodium increases from the outer surface to the inner part, and the concentration of manganese decreases from the outer surface to the inner part;

[0008] The core has a composition shown in Formula II: Na n Ni x Mn y Fe z M 1 k O2, where 0.8 ≤ n ≤ 1.05, 0.2 ≤ x ≤ 0.4, 0.2 ≤ y ≤ 0.4, 0.2 ≤ z ≤ 0.4, 0.03 ≤ k ≤ 0.12, M 1 One or more selected from Ti, Mg, Zn, Li, Cu, Zr, Y, Ce, La, Sm, Se, Sr, Nb and V;

[0009] The coating layer has a composition shown in formula III: Na α Ni β Mn γ M 2 δ O2, where 0.5≤ α≤ 0.7, 0.2≤ β≤ 0.33, 0.33≤ γ≤ 0.75, 0≤ δ≤ 0.33, M 2 One or more selected from Ti, Mg, Zn, Li, Al, B, Ce, Sr, Ta and Nb;

[0010] The molar ratio of sodium to all metals except sodium in the inner core is 0.8-1.3:1; the total molar ratio of sodium to all metals except sodium in the coating layer is 0.5-0.9:1; the inner core is an O3 type structure, and the coating layer is a P2 type structure.

[0011] Preferably, the cathode material has a composition as shown in Formula I: Na e Nia Mn b Fe c M d O2, wherein 0.89 ≤ e ≤1, 0.25 ≤ a ≤ 0.35, 0.28 ≤ b ≤ 0.45, 0.2 ≤ c ≤ 0.4, and 0.03 ≤ d ≤ 0.16; and M is selected from one or more of Ti, Mg, Zn, Li, Al, B, Cu, Zr, Y, Ce, La, Sm, Sr, Nb, Ta, and V.

[0012] Preferably, the core has a composition shown in Formula II: Na n Ni x Mn y Fe z M 1 k O2, where 0.8 ≤ n ≤1.05, 0.25 ≤ x ≤ 0.35, 0.28 ≤ y ≤ 0.33, 0.3≤z ≤0.35, 0.04 ≤ k ≤ 0.1; M 1 One or more selected from Ti, Mg, Zn, Li, Cu, Sm and Zr.

[0013] Preferably, the coating layer has a composition shown in formula III: Na α Ni β Mn γ M 2 δ O2, where 0.6≤ α≤ 0.7, 0.23≤ β≤ 0.33, 0.33≤ γ≤ 0.67, 0.05≤ δ≤ 0.33, M 2 One or more selected from Ti, Mg, Zn, Li, Al and B.

[0014] More preferably, the coating layer has a composition shown in formula III: Na α Ni β Mn γ M 2 δ O2, where 0.6≤ α≤0.7, 0.23≤ β≤ 0.33, 0.33≤ γ≤ 0.67, 0.1≤ δ≤ 0.33; M 2 One or more selected from Ti, Mg, Zn, Li, Al and B.

[0015] More preferably, the coating layer has a composition shown in formula III: Na α Ni β Mn γ M 2δ O2, where 0.6≤ α≤0.7, 0.23≤ β≤ 0.33, 0.33≤ γ≤ 0.67, 0.1≤ δ≤ 0.2; M 2 One or more selected from Ti, Mg, Zn, Li, Al and B.

[0016] Preferably, the total molar ratio of sodium to all metals except sodium in the inner core is 0.8-1.1:1.

[0017] More preferably, the total molar ratio of sodium to all metals except sodium in the inner core is 0.9-1.1:1;

[0018] Preferably, the total molar ratio of sodium to all metals except sodium in the coating layer is 0.6-0.8:1.

[0019] More preferably, the total molar ratio of sodium to all metals except sodium in the inner core is higher than the total molar ratio of sodium to all metals except sodium in the coating layer.

[0020] Preferably, the particle size of the core is 1-20 μm.

[0021] Preferably, the particle size of the core is 1-10 μm.

[0022] Preferably, the coating layer has a thickness of 10 to 200 nm.

[0023] Preferably, the coating layer has a thickness of 20-150 nm.

[0024] In a second aspect, the present invention provides a method for preparing the positive electrode material having a gradient structure, comprising the following steps:

[0025] S1: mixing the raw materials of the core material with the first dispersant, and calcining them twice to obtain the core material;

[0026] S2: Mix the raw materials of the core material and the coating layer material with the second dispersant, and calcine them twice to obtain the positive electrode material with the gradient structure.

[0027] Preferably, the M source is selected from oxides of one or more elements selected from Ti, Mg, Zn, Li, Al, B, Cu, Cr, Zr, Y, Ce, La, Sm, Se, Sr, Nb, W, Ta and V, their salts or their organic matter.

[0028] Preferably, the M source is selected from carbonates, oxalates, hydroxides, nitrates or oxides of one or more elements selected from Ti, Mg, Zn, Mg, Li, Al, B, Cu, Zr, Sm and Nb.

[0029] More preferably, the M source comprises one or more of zinc oxide, zinc nitrate, titanium oxide, magnesium oxide, magnesium carbonate, magnesium hydroxide, lithium carbonate, lithium hydroxide, aluminum nitrate, aluminum oxide, boron oxide, copper carbonate, copper oxide, copper oxalate, zirconium oxide, samarium oxide and niobium oxide.

[0030] Preferably, in step S1, the raw materials of the core material are mixed with the first dispersant in a stoichiometric ratio by a solid phase mixing method.

[0031] Preferably, the solid phase mixing method is a ball milling mixing method.

[0032] More preferably, the ball milling time is 6 to 12 h.

[0033] Preferably, the ball-to-material ratio during ball milling is 2-10:1.

[0034] Preferably, the rotational speed during ball milling is 200-600 r / min.

[0035] Preferably, in step S1, the conditions for the first calcination are: a heating rate of 1-5 °C / min, a calcination temperature of 850-1050 °C, and / or a calcination time of 10-20 h; the conditions for the second calcination are: a heating rate of 1-5 °C / min, a calcination temperature of 750-950 °C, and a calcination time of 5-10 h.

[0036] Preferably, after the first calcination, the temperature is lowered to below 300° C., and then the temperature is raised again for the second calcination.

[0037] Preferably, the atmosphere of the first calcination is an atmosphere containing oxygen.

[0038] Preferably, the atmosphere is oxygen and / or air.

[0039] Preferably, the atmosphere of the second calcination is one or more of oxygen, air or nitrogen.

[0040] Preferably, in step S2, the core material, the raw materials of the coating layer material in a stoichiometric ratio and the second dispersant are mixed by a solid phase mixing method.

[0041] Preferably, the solid phase mixing method is a ball milling mixing method.

[0042] More preferably, the ball milling time is 6 to 12 h.

[0043] Preferably, the ball-to-material ratio during ball milling is 2-5:1.

[0044] Preferably, the rotational speed during ball milling is 100-400 r / min.

[0045] Preferably, in step S2, the conditions for the first calcination are: a heating rate of 1-5 °C / min, a calcination temperature of 850-1050 °C, and / or a calcination time of 10-20 h; the conditions for the second calcination are: a heating rate of 1-5 °C / min, a calcination temperature of 750-950 °C, and a calcination time of 5-10 h.

[0046] Preferably, after the first calcination, the temperature is lowered to below 300° C., and then the temperature is raised for the second calcination;

[0047] Preferably, the atmosphere of the first calcination is an atmosphere containing oxygen.

[0048] Preferably, the atmosphere is oxygen and / or air.

[0049] Preferably, the atmosphere of the second calcination is one or more of oxygen, air or nitrogen.

[0050] Preferably, the first dispersant is ethanol, acetone or water.

[0051] Preferably, the second dispersant is ethanol, acetone or water.

[0052] Preferably, the molar ratio of the coating layer material to the core material is 1:1.5-20.

[0053] Preferably, the molar ratio of the coating layer material to the core material is 1:2-20.

[0054] Preferably, the molar ratio of the coating layer material to the core material is 1:1.5-2.8.

[0055] Preferably, a positive electrode material for a sodium ion battery is prepared by the method for preparing the positive electrode material with a gradient structure.

[0056] In a third aspect, the present invention provides a sodium ion battery positive electrode, which comprises the sodium ion battery positive electrode material with a gradient structure as a positive electrode active material.

[0057] In a fourth aspect, the present invention provides a sodium ion battery, which comprises the sodium ion battery positive electrode, negative electrode and an electrolyte containing sodium salt.

[0058] In a fifth aspect, the present invention provides an application of the sodium ion battery as a power source in photovoltaic, electric power, energy storage system or mobile storage device or low-end electric vehicle;

[0059] And / or, the use of the sodium ion battery in distributed energy storage, centralized energy storage or low-end power battery energy storage devices.

[0060] In a sixth aspect, the present invention provides a power system, an energy storage system or a mobile storage device, characterized in that it is prepared by the sodium ion battery described above.

[0061] Beneficial effects of the present invention

[0062] (1) The present invention obtains a layered oxide material with a gradient structure by coating the material on the surface of the core, which has both high-pressure performance and air stability. The present invention adjusts the composition ratio of the core material and the coating layer material in the composite material so that the sodium element concentration and the manganese element concentration present a gradient structure, where the sodium element concentration increases from the outer surface to the inner part, and the manganese element concentration decreases from the outer surface to the inner part. This special structure can further effectively improve the high-pressure stability and air stability of the material.

[0063] (2) The composite layered oxide positive electrode material of the present invention can ensure the dual requirements of positive electrode material energy density and stable storage in practical applications, and the preparation process is simple and highly repeatable.

[0064] (3) The composite layered oxide positive electrode material of the present invention has excellent air stability and specific capacity. In the sodium ion battery half-cell test, the gram-specific capacity at 2.0-4.3 V at a rate of 0.1C is not less than 145 mAh / g, the capacity retention rate after 100 cycles at 1C is above 89%, and the capacity retention rate after 800 cycles at 5C is above 71%. There is no capacity loss after being stored in an environment with a humidity of 80% for 3 days, and there is no obvious change in structure after being stored in an environment with a humidity of 40% for 93 days. BRIEF DESCRIPTION OF THE DRAWINGS

[0065] Figure 1 This is a scanning electron microscope image of the core material obtained in Example 1 of the present invention.

[0066] Figure 2 This is a scanning electron microscope image of the core material obtained in Example 2 of the present invention.

[0067] Figure 3 The transmission electron microscope images of the composite layered oxide positive electrode material for sodium ion batteries obtained in Example 1 of the present invention are shown in FIG. (a) is a TEM image of the composite layered oxide positive electrode material; and (b) is a HRTEM image of the composite layered oxide positive electrode material.

[0068] Figure 4 This is the XRD diffraction pattern of the sodium ion battery composite layered oxide positive electrode material obtained in Example 1 of the present invention.

[0069] Figure 5 The graph is a cycle performance diagram of the positive electrode materials obtained in Example 1 and Comparative Example 1 at 2-4.3 V and 5 C current density.

[0070] Figure 6 The graph is a cycle performance diagram of the positive electrode materials obtained in Example 1 and Comparative Example 1 at 2~4.3 V and 1 C current density.

[0071] Figure 7 Figure 1 is the XRD diffraction pattern and scanning electron microscope image of the positive electrode materials obtained in Example 1 and Comparative Example 1 after being placed in an environment with a humidity of 40% RH for 93 days. (a) is the XRD diffraction pattern of the positive electrode material obtained in Example 1 after being placed in an environment with a humidity of 40% RH for 93 days, and the inset is the scanning electron microscope image. (b) is the XRD diffraction pattern of the positive electrode material obtained in Comparative Example 1 after being placed in an environment with a humidity of 40% RH for 93 days, and the inset is the scanning electron microscope image.

[0072] Figure 8 The graph is a cycle performance diagram of the positive electrode materials obtained in Example 1 and Comparative Example 1 at 2-4.3 V and 1 C current density after being placed in an environment with a humidity of 80% RH for 3 days.

[0073] Fig. 9 The scanning electron microscope image of the cross-section of the positive electrode material particles obtained in Example 1 and the EDS line scan mode are the data diagrams of the distribution content of the tested sodium element in the particles from left to right.

[0074] Fig.10 This is a data diagram of the distribution content of manganese element in the particles tested from left to right in the EDS line scan mode of the positive electrode material particle surface obtained in Example 1.

[0075] Fig.11 for Fig. 9 and Fig.10 Annotated image of a composite material particle. DETAILED DESCRIPTION

[0076] As described above, the object of the present invention is to provide a sodium ion battery positive electrode material with a gradient structure and a preparation method and application thereof.

[0077] The present invention controls and designs a gradient structure in which the sodium concentration increases from the outer surface to the inner part and the manganese concentration decreases from the outer surface to the inner part, thereby ensuring that part of the sodium ions exist between the alkali metal layers and play the role of interlayer pillars during high-voltage charging and discharging, so as to obtain a highly stable layered oxide positive electrode material for sodium ion batteries. At the same time, in the prior art, materials without electrochemical activity such as aluminum oxide or zinc oxide are often used as coating layers, which show a decrease in overall capacity after coating. The present invention, by combining a material with a high sodium content and high specific capacity in the inner core and a sodium-deficient stable material in the coating layer, that is, a composite of an inner core full of sodium O3 type positive electrode material and an outer layer sodium-deficient P2 type positive electrode material, can make the composite material circulate stably at a higher voltage, improve the working voltage and capacity of the composite material, and show a higher energy density.

[0078] In the present invention, the positive electrode material with a gradient structure means that: the sodium concentration of the positive electrode material gradually decreases from the inside to the outside (the outside is the direction close to the surface of the composite material); the manganese concentration gradually increases from the inside to the outside. Among them, in the gradient structure, the concentration of the element can be uniformly increased or decreased from the inside to the surface of the positive electrode material, or it can be unevenly increased or decreased, but it must satisfy the trend of increasing or decreasing from the inside to the outside.

[0079] In a first aspect, the present invention provides a positive electrode material having a gradient structure, wherein the positive electrode material is a core-shell structure, which includes a core and a coating layer; the positive electrode material has a composition shown in Formula I: Na e Ni a Mn b Fe c M d O2, wherein, 0.8≤ e ≤ 1.05, 0.2 ≤ a ≤ 0.35, 0.2 ≤ b ≤ 0.5, 0.15 ≤ c ≤ 0.4, 0.01≤ d ≤0.16, M is selected from one or more of Ti, Mg, Zn, Li, Al, B, Cu, Cr, Zr, Y, Ce, La, Sm, Se, Sr, Nb, W, Ta and V; the concentration of sodium element increases gradiently from the outer surface to the inner part, and the concentration of manganese element decreases gradiently from the outer surface to the inner part.

[0080] Preferably, the cathode material has a composition as shown in Formula I: Na e Ni a Mn b Fe c M d O2, wherein 0.89 ≤ e ≤1, 0.25 ≤ a ≤ 0.35, 0.28 ≤ b ≤ 0.45, 0.2 ≤ c ≤ 0.4, 0.03 ≤ d ≤ 0.16; M is selected from one or more of Ti, Mg, Zn, Li, Al, B, Cu, Cr, Zr, Y, Ce, La, Sm, Se, Sr, Nb, W, Ta and V.

[0081] Preferably, the cathode material has a composition as shown in Formula I: Na e Ni a Mn b Fe c M dO2, wherein 0.89 ≤ e ≤1, 0.25 ≤ a ≤ 0.35, 0.28 ≤ b ≤ 0.45, 0.2 ≤ c ≤ 0.4, and 0.03 ≤ d ≤ 0.16; and M is selected from one or more of Ti, Mg, Zn, Li, Al, B, Cu, Zr, Y, Ce, La, Sm, Sr, Nb, Ta, and V.

[0082] Preferably, the molar ratio of sodium to all metals except sodium in the inner core is 0.8-1.3:1; the total molar ratio of sodium to all metals except sodium in the coating layer is 0.5-0.9:1; the total molar ratio of sodium to all metals except sodium in the inner core is higher than the total molar ratio of sodium to all metals except sodium in the coating layer.

[0083] In the present invention, when the molar ratio of sodium to the total metals other than sodium in the core material exceeds the specified range, it indicates that there is too high sodium content in the core material, which is easy to cause excessive residual alkali on the surface. Excessive residual alkali will cause the material to agglomerate during the coating process of the slurry, and the surface side reactions will intensify when the battery is running, which is not conducive to the electrochemical performance of the material; and when the molar ratio of sodium to the total metals other than sodium in the core material is lower than the specified range, it indicates that the sodium content in the core material is less, the specific capacity of the material is low, and the capacity advantage of the material cannot be fully exerted. When the molar ratio of sodium to the total metals other than sodium in the coating material exceeds the specified range, the sodium content of the coating layer material is high, which is not conducive to the formation of the P2 phase in the outer layer of the core when coated with the core material, and is not conducive to the air stability and rate performance of the composite material. When the molar ratio of sodium to the total metals other than sodium in the coating material is lower than the specified range, the sodium content of the coating layer material is less, and the overall sodium content of the composite material formed when coated with the core material is low, and the material exhibits a lower specific capacity, which is not conducive to the advantages of the composite material.

[0084] Preferably, the core has a composition shown in Formula II: Na n Ni x Mn y Fe z M 1 k O2, where 0.8 ≤ n ≤1.05, 0.2 ≤ x ≤ 0.4, 0.2 ≤ y ≤ 0.4, 0.2≤z ≤0.4, 0.03≤ k ≤0.12, M 1 One or more selected from Ti, Mg, Zn, Li, Cu, Zr, Y, Ce, La, Sm, Se, Sr, Nb and V.

[0085] Preferably, the core has a composition shown in Formula II: Na n Ni x Mny Fe z M 1 k O2, where 0.8 ≤ n ≤1.05, 0.25 ≤ x ≤ 0.35, 0.28 ≤ y ≤ 0.33, 0.3≤z ≤0.35, 0.04 ≤ k ≤ 0.1; M 1 One or more selected from Ti, Mg, Zn, Li, Cu, Zr, Y, Ce, La, Sm, Se, Sr, Nb and V.

[0086] Preferably, the core has a composition shown in Formula II: Na n Ni x Mn y Fe z M 1 k O2, where 0.8 ≤ n ≤1.05, 0.2 ≤ x ≤ 0.4, 0.2 ≤ y ≤ 0.4, 0.2≤z ≤0.4, 0.03≤ k ≤0.12, M 1 One or more selected from Ti, Mg, Zn, Li, Cu, Sm and Zr.

[0087] Preferably, the core has a composition shown in Formula II: Na n Ni x Mn y Fe z M 1 k O2, where 0.8 ≤ n ≤1.05, 0.25 ≤ x ≤ 0.35, 0.28 ≤ y ≤ 0.33, 0.3≤z ≤0.35, 0.04 ≤ k ≤ 0.1; M 1 One or more selected from Ti, Mg, Zn, Li, Cu, Sm and Zr.

[0088] More preferably, M 1 One or more selected from Mg, Li, Cu, Sm and Zr.

[0089] Preferably, the coating layer has a composition shown in formula III: Na α Ni β Mn γ M 2 δ O2, where, 0.5≤ α≤ 0.7, 0.2≤ β ≤0.33, 0.33≤ γ ≤0.75, 0≤ δ ≤0.33, M 2Includes one or more of Ti, Mg, Zn, Li, Al, B, Ce, Sr, Ta and Nb.

[0090] Preferably, the coating layer has a composition shown in formula III: Na α Ni β Mn γ M 2 δ O2, where 0.6≤ α≤ 0.7, 0.23≤ β≤ 0.33, 0.33≤ γ≤ 0.67, 0.05≤ δ≤ 0.33; M 2 Includes one or more of Ti, Mg, Zn, Li, Al, B, Ce, Sr, Ta and Nb.

[0091] More preferably, the coating layer has a composition shown in formula III: Na α Ni β Mn γ M 2 δ O2, where 0.6≤ α≤0.7, 0.23≤ β≤ 0.33, 0.33≤ γ≤ 0.67, 0.1≤ δ≤ 0.33; M 2 Includes one or more of Ti, Mg, Zn, Li, Al, B, Ce, Sr, Ta and Nb.

[0092] More preferably, the coating layer has a composition shown in formula III: Na α Ni β Mn γ M 2 δ O2, where 0.6≤ α≤0.7, 0.23≤ β≤ 0.33, 0.33≤ γ≤ 0.67, 0.1≤ δ≤ 0.2; M 2 Includes one or more of Ti, Mg, Zn, Li, Al, B, Ce, Sr, Ta and Nb.

[0093] Preferably, the coating layer has a composition shown in formula III: Na α Ni β Mn γ M 2 δ O2, where, 0.5≤ α≤ 0.7, 0.2≤ β ≤0.33, 0.33≤ γ ≤0.75, 0≤ δ ≤0.33, M 2 One or more selected from Ti, Mg, Zn, Li, Al and B.

[0094] Preferably, the coating layer has a composition shown in formula III: Na α Ni β Mn γ M 2 δ O2, where 0.6≤ α≤ 0.7, 0.23≤ β≤ 0.33, 0.33≤ γ≤ 0.67, 0.05≤ δ≤ 0.33; M 2 One or more selected from Ti, Mg, Zn, Li, Al and B.

[0095] More preferably, the coating layer has a composition shown in formula III: Na α Ni β Mn γ M 2 δ O2, where 0.6≤ α≤0.7, 0.23≤ β≤ 0.33, 0.33≤ γ≤ 0.67, 0.1≤ δ≤ 0.33; M 2 One or more selected from Ti, Mg, Zn, Li, Al and B.

[0096] More preferably, the coating layer has a composition shown in formula III: Na α Ni β Mn γ M 2 δ O2, where 0.6≤ α≤0.7, 0.23≤ β≤ 0.33, 0.33≤ γ≤ 0.67, 0.1≤ δ≤ 0.2; M 2 One or more selected from Ti, Mg, Zn, Li, Al and B.

[0097] More preferably, M 2 One or more selected from Mg, Li, Al and B.

[0098] Preferably, the content of manganese in the core is lower than the content of manganese in the coating layer.

[0099] Preferably, the core has a composition shown in Formula II: Na n Ni x Mn y Fe z M 1 k O2, where 0.8 ≤ n ≤1.05, 0.2 ≤ x ≤ 0.4, 0.2 ≤ y ≤ 0.4, 0.2≤z ≤0.4, 0.03≤ k ≤0.12; M 1One or more selected from Ti, Mg, Zn, Li, Cu, Sm and Zr; the coating layer has a composition shown in formula III: Na α Ni β Mn γ M 2 δ O2, where 0.5≤ α≤ 0.7, 0.2≤ β≤ 0.33, 0.33≤ γ≤ 0.75, 0≤ δ≤ 0.33, M 2 One or more selected from Ti, Mg, Zn, Li, Al and B.

[0100] Preferably, M 1 Zn, M 2 One or more selected from Ti, Mg, Zn, Li, Al, B, Ce, Sr, Ta and Nb. When synthesizing the O3 phase positive electrode material, the zinc element has a fluxing effect, which is beneficial to improve the crystallinity of the material and reduce the formation of nickel oxide impurities during the calcination process. When the core contains zinc, nickel oxide impurities are not easy to appear.

[0101] More preferably, M 1 Zn, M 2 One or more selected from Ti, Mg, Zn, Li, Al and B.

[0102] Preferably, M 1 One or more selected from the group consisting of Ti, Mg, Li, Cu, Zr, Y, Ce, La, Sm, Se, Sr, Nb and V; M 2 It is Zn and any one or a combination of two or more selected from the following elements: Ti, Mg, Zn, Li, Al, B, Ce, Sr, Ta and Nb.

[0103] Preferably, M 1 One or more selected from the group consisting of Ti, Mg, Li, Cu, Zr, Y, Ce, La, Sm, Se, Sr, Nb and V; M 2 One or more selected from Nb, Ti, Al, B and Ta; wherein M 2 The ion radius of M must be smaller than that of divalent nickel ions. 2 The ionic radius is large, and nickel oxide impurities are likely to appear in the material after coating, which is not conducive to the formation of a two-phase structure and has an adverse effect on the electrochemical properties of the material, resulting in a decrease in material activity and a decrease in specific capacity.

[0104] The composition of the inner core described in the present invention, namely Formula II, is a theoretical chemical formula obtained according to the feed ratio (in terms of metal atoms) of the metal source (except the sodium source). The content of sodium in Formula II is 5% less than the feed amount of the sodium source, mainly considering that the sodium element will be lost during the sintering process. For example, the subscript of sodium in Formula II is 1, and the feed ratio of the sodium source (in terms of metal atoms) is 1.05. Similarly, the composition of the coating layer described in the present invention, namely Formula III, is a theoretical chemical formula obtained according to the feed ratio (in terms of metal atoms) of the metal source (except the sodium source). The content of sodium in Formula III is 5% less than the feed amount of the sodium source, mainly considering that the sodium element will be lost during the sintering process. For example, the subscript of sodium in Formula III is 0.67, and the feed ratio of the sodium source (in terms of metal atoms) is 0.7.

[0105] In the present invention, the kernel generally selects an O3 type structural material containing a high content of Na, Ni and Fe, and the coating material does not contain iron elements, and mainly contains Ni and Mn elements, which are P2 phase materials, and is compounded with the kernel material of the O3 phase. By regulating the combination ratio of the two, a synergistic effect is exerted, so that the cycle stability and capacity of the composite positive electrode material are better exerted. Among them, the content of the Mn element in the coating layer needs to be higher than the content of the Mn element in the kernel. The structure ensures that the outer layer has a higher manganese content to reduce the high-valent nickel and iron elements enriched on the surface during high-voltage charging and discharging, otherwise the high-valent nickel-iron elements have a higher activity and will have serious side reactions with the electrolyte, reducing the cycle stability of the material. In addition, the molar ratio of the sodium content in the kernel to the total content of metals other than sodium is higher than the molar ratio of the sodium content in the coating layer to the total content of metals other than sodium, and the structure obtains better cycle stability and air stability; the kernel sodium content in the composite structure is high and diffuses from the inside to the outside, and a small amount of sodium ions will remain on the outside to play the role of a pillar, maintaining the stability of the structure, and thus can improve the electrochemical performance of the material.

[0106] Preferably, during the coating process, through calcination treatment, the high-concentration sodium in the inner core diffuses into the outer shell with a low sodium content under kinetic and thermodynamic control to form a layered material with a sodium concentration gradient structure.

[0107] Preferably, during the coating process, through calcination treatment, the high-concentration manganese element in the coating layer is controlled by kinetics and thermodynamics to diffuse into the inner core with a low manganese content to form a layered material with a manganese concentration gradient structure.

[0108] In the present invention, the particle size is the diameter of spherical particles or the diameter of round cake-shaped particles.

[0109] The second object of the present invention is to provide a method for preparing a composite positive electrode material, comprising the following steps:

[0110] (1) mixing the raw materials of the core material with the first dispersant by ball milling according to a stoichiometric ratio, and calcining twice to obtain the core material;

[0111] (2) The core material, the raw materials of the coating layer material in a stoichiometric ratio, and the second dispersant are ball-milled and mixed, and the mixture is calcined twice to obtain the composite positive electrode material.

[0112] Preferably, the raw materials of the core material and the coating layer material include a Na source, a Ni source, a Mn source, a Fe source or a M source.

[0113] Preferably, the Na source includes but is not limited to one or more of sodium hydroxide, sodium carbonate, sodium nitrate, sodium oxalate and sodium acetate.

[0114] Preferably, the Ni source includes but is not limited to one or more of nickel oxide, nickel acetate, nickel nitrate, nickel hydroxide and nickel carbonate.

[0115] Preferably, the Mn source includes, but is not limited to, one or more of manganese dioxide, manganese trioxide, manganese tetraoxide, manganese acetate, manganese nitrate and manganese carbonate.

[0116] Preferably, the Fe source includes, but is not limited to, one or more of ferric oxide, ferric oxide, ferric nitrate, ferric oxalate, and ferric acetate.

[0117] Preferably, the first calcination temperature is higher than the second calcination temperature. If the second calcination temperature is too high, the sodium in the positive electrode material will volatilize. Properly lowering the temperature helps the sodium remaining on the surface of the material obtained by the first calcination to enter the bulk structure, thereby increasing the material specific capacity.

[0118] Preferably, in step (1) or step (2), the atmosphere of the first calcination is an atmosphere containing oxygen; preferably, the atmosphere is oxygen and / or air; and / or, the atmosphere of the second calcination is one or more of oxygen, air and nitrogen.

[0119] During the calcination process, the different oxygen content in the calcination atmosphere will affect the valence ratio of non-sodium metals. Generally speaking, the higher the oxygen content, the more high-valence states of non-sodium metals. When the oxygen content is lower, the number of low-valence states of non-sodium metals will increase. The valence of non-sodium metals will affect the cycle stability and capacity of the positive electrode material.

[0120] Preferably, the molar ratio of the coating layer material to the core material is 1:2 to 20. The molar ratio of the coating layer material to the core material will affect the high voltage performance of the battery positive electrode material.

[0121] Preferably, a higher ball milling speed and a larger ball-to-material ratio are used to prepare the core material, and a smaller ball milling speed and a smaller ball-to-material ratio are used when coating the core material surface. This is because milder ball milling conditions are used to avoid destruction of the crystal phase of the core material during coating.

[0122] In the present invention, the calcination temperature has a great influence on the performance of the composite positive electrode material. Too high a calcination temperature is not conducive to the formation of a two-phase structure. At the same time, sodium will be lost at high temperature, resulting in a decrease in the material capacity. At the same time, the present invention is conducive to improving the crystallinity of the material by setting a secondary calcination process, and at the same time promotes more residual sodium on the surface to migrate into the inner core, thereby reducing the residual alkali content on the surface of the material. In addition, the heating rate of the calcined material also has a great influence on the crystallinity of the material. The heating rate should be no more than 5°C / min, which is more conducive to the crystallization of the composite material.

[0123] In the present invention, the ball-to-grinding material ratio refers to the weight ratio of the balls to the added materials; for example, a ball-to-grinding material ratio of 10:1 means: the weight of the balls is 10 parts by weight, and the weight of the materials is 1 part by weight.

[0124] Unless otherwise specified, the various reagents / instruments used in the examples and comparative examples of the present invention are conventional commercially available products. The experimental materials and instrument information used in the present invention are shown in Table 1 below:

[0125]

[0126] In order to better understand the technical solution of the present invention, the technical solution of the present invention is described in detail below in conjunction with specific embodiments.

[0127] Example 1

[0128] (1) Sodium carbonate, iron oxide, nickel oxide, manganese oxide and zinc oxide were taken according to the molar ratio of metal elements of 1.05:0.33:0.26:0.33:0.07, and the materials were placed in the ball mill of a planetary ball mill. Ethanol was added as a dispersant, and the ball milling speed was controlled to 300 r / min. The ball milling ratio was 10:1, and the ball milling was carried out for 6 h. Finally, the obtained material was dried at 80 °C for 12 h to obtain a ball-milled precursor.

[0129] (2) The precursor powder obtained in step (1) was placed in an alumina crucible, and the crucible was placed in a muffle furnace for secondary calcination. The temperature was raised to 900 °C at 5 °C / min for the first calcination, and the temperature was kept at this temperature for 15 h, and the temperature was naturally cooled to room temperature. Then, the temperature was raised to 850 °C at 5 °C / min for the second calcination, and the temperature was kept at this temperature for 8 h, and the temperature was naturally cooled to room temperature. The atmosphere for both calcinations was air. After the sintering process was completed, the inner core layered oxide material A was obtained, and its scanning electron microscope image was shown as follows: Figure 1As shown in the figure, it can be seen that the morphology of the synthesized core layered oxide material A is similar to a round cake, and its diameter is taken as the particle size of material A, which is about 5~10 μm. In terms of the amount of metal elements, the chemical formula of the core layered oxide material A is: NaNi 0.26 Mn 0.33 Fe 0.33 Zn 0.07 O2.

[0130] (3) Adding layered oxide material A to a ball mill, adding sodium carbonate, nickel oxide and manganese oxide to the ball mill, mixing them in a molar ratio of 0.7:0.33:0.67 of metal elements to synthesize a coating layer layered oxide material B. The chemical formula of the coating layer material B is: Na 0.67 Ni 0.33 Mn 0.67 O2, wherein the molar ratio of the added core layered oxide material A and the coating layer material B is 2:1, acetone is added as a dispersant, and the ball milling is carried out at 200 r / min, the ball milling ratio is 5:1, and after 12 hours of ball milling, it is placed in a vacuum drying oven at 80°C for 2 hours, and the dried material is placed in an alumina crucible in a muffle furnace, and the secondary calcination is adopted, and the temperature is increased to 900°C at 5°C / min for the first calcination. After the heat preservation time is 15 hours, it is naturally cooled to room temperature; then the temperature is increased to 850°C at 5°C / min for the second calcination. After the heat preservation time is 8 hours, it is naturally cooled to room temperature. The atmosphere of the two calcinations is air. After the sintering procedure is completed, the composite layered oxide material Na 0.89 Ni 0.283 Mn 0.443 Fe 0.22 Zn 0.047 O2.

[0131] Among them, the composite layered oxide material Na 0.89 Ni 0.283 Mn 0.443 Fe 0.22 Zn 0.047 Transmission electron microscopy image of O2 Figure 3 As shown, from Figure 3 As can be seen from (a) in the figure, the relatively lighter color area is the coating layer of the composite layered oxide material, and the thickness of the coating layer is 50~100 nm. Figure 3 As can be seen from (b), the color from light to dark indicates the direction from the outside to the inside of the composite layered oxide material. The P2 phase is in the lighter color, which is the outside of the composite layered oxide material, and the O3 phase is in the darker color, which is the inside of the composite layered oxide material. That is, the composite layered oxide material is a two-phase structure layered material. Its XRD diffraction pattern is as follows: Figure 4As shown, the diffraction peaks at 16.0° and 39.5° are obvious characteristic diffraction peaks of the P2 phase, and the diffraction peaks at 16.4° and 41.8° are obvious characteristic diffraction peaks of the O3 phase. Therefore, the composite layered oxide material is a P2 / O3 two-phase composite structure.

[0132] Example 2

[0133] Compared with Example 1, the raw materials in step (1) are "sodium carbonate, iron oxide, nickel oxide, manganese oxide and titanium oxide are taken according to the metal element molar ratio of 1.05:0.33:0.33:0.28:0.05", and the other parameters and steps are the same as those in Example 1. The chemical formula of the obtained inner core layered oxide material A is: NaNi 0.33 Mn 0.28 Fe 0.33 Ti 0.05 O2; the chemical formula of coating material B is: Na 0.67 Ni 0.33 Mn 0.67 O2; the composite layered oxide is Na 0.89 Ni 0.33 Mn 0.41 Fe 0.22 Ti 0.033 O2.

[0134] Among them, the scanning electron microscope image of the core layered oxide material A is as follows Figure 2 As shown in the figure, it can be seen that the morphology of the synthesized inner core layered oxide material A is irregular spherical and round cake-shaped. According to the diameter of the irregular spherical particles and the diameter of the round cake-shaped particles, the particle size of the inner core layered oxide material A is measured to be 1~5μm; the thickness of the coating layer is about 50~100nm.

[0135] Example 3

[0136] Compared with Example 1, the raw materials in step (1) are "sodium carbonate, iron oxide, nickel oxide, manganese oxide and magnesium oxide are taken according to the metal element molar ratio of 1.05:0.33:0.28:0.33:0.05", and the other parameters and steps are the same as those in Example 1. The chemical formula of the obtained inner core layered oxide material A is: NaNi 0.28 Mn 0.33 Fe 0.33 Mg 0.05 O2; the chemical formula of coating material B is: Na 0.67 Ni 0.33 Mn 0.67 O2; the composite layered oxide is Na 0.89 Ni 0.297 Mn 0.443 Fe 0.22 Mg 0.033O2.

[0137] The morphology of the inner core layered oxide material A is irregular spherical and round, with a particle size of 1-5 μm; the thickness of the coating layer is about 50-100 nm.

[0138] Example 4

[0139] Compared with Example 1, the raw materials in step (3) are "sodium carbonate, nickel oxide, manganese oxide, and zinc oxide are mixed according to the molar ratio of metal elements 0.7:0.247:0.67:0.083", and the other parameters and steps are the same as those in Example 1. The chemical formula of the obtained inner core layered oxide material A is: NaNi 0.26 Mn 0.33 Fe 0.33 Zn 0.07 O2; the chemical formula of coating material B is: Na 0.67 Ni 0.247 Mn 0.67 Zn 0.083 O2; the composite layered oxide is Na 0.89 Ni 0.256 Mn 0.443 Fe 0.22 Zn 0.074 O2.

[0140] The morphology of the inner core layered oxide material A is irregular spherical and round, with a particle size of 5-10 μm; the thickness of the coating layer is about 50-100 nm.

[0141] Example 5

[0142] Compared with Example 1, the raw materials in step (3) are "sodium carbonate, nickel oxide, manganese oxide, and lithium carbonate mixed in a molar ratio of 0.7:0.23:0.67:0.1 for the metal elements", and the remaining parameters and steps are the same as those in Example 1. The chemical formula of the obtained inner core layered oxide material A is: NaNi 0.26 Mn 0.33 Fe 0.33 Zn 0.07 O2; the chemical formula of coating material B is: Na 0.67 Ni 0.23 Mn 0.67 Li 0.1 O2; the obtained composite layered oxide is: Na 0.89 Ni 0.25 Mn 0.443 Fe 0.22 Zn 0.047 Li 0.033 O2.

[0143] The morphology of the inner core layered oxide material A is irregular spherical and round, with a particle size of about 5-10 μm and a coating layer thickness of about 50-100 nm.

[0144] Example 6

[0145] Compared with Example 1, the raw materials in step (3) are "sodium carbonate, nickel oxide, manganese oxide, and titanium oxide mixed in a molar ratio of 0.7:0.33:0.44:0.22 for the metal elements", and the remaining parameters and steps are the same as those in Example 1. The chemical formula of the obtained inner core layered oxide material A is: NaNi 0.26 Mn 0.33 Fe 0.33 Zn 0.07 O2; the chemical formula of coating material B is: Na 0.67 Ni 0.33 Mn 0.44 Ti 0.22 O2; the obtained composite layered oxide is: Na 0.89 Ni 0.283 Mn 0.367 Fe 0.22 Zn 0.047 Ti 0.073 O2.

[0146] The morphology of the inner core layered oxide material A is irregular spherical and round, with a particle size of about 5-10 μm and a coating layer thickness of about 50-100 nm.

[0147] Example 7

[0148] (1) Sodium carbonate, iron oxide, nickel oxide, manganese oxide and titanium oxide were taken according to the molar ratio of metal elements of 1.05:0.2:0.25:0.3:0.04, and the materials were placed in the ball mill of a planetary ball mill. Ethanol was added as a dispersant, and the ball milling speed was controlled to 300 r / min. The ball milling ratio was 10:1, and the ball milling was carried out for 6 h. Finally, the obtained material was dried at 80 °C for 12 h to obtain a ball-milled precursor.

[0149] (2) The precursor powder obtained in step (1) is placed in an alumina crucible, and the crucible is placed in a muffle furnace. The crucible is subjected to secondary calcination. The temperature is raised to 900 °C at 5 °C / min, and the first calcination is carried out. The temperature is kept at this temperature for 15 h, and the temperature is naturally cooled to room temperature. Then, the temperature is raised to 850 °C at 5 °C / min, and the second calcination is carried out. The temperature is kept at this temperature for 8 h, and the temperature is naturally cooled to room temperature. The atmosphere for both calcinations is air. After the sintering process is completed, the inner core layered oxide material A is obtained. The morphology of the inner core layered oxide material A is irregular spherical and round cake-shaped, with a particle size of 1-5 μm. In terms of the amount of metal elements, the chemical formula of the inner core layered oxide material A is: NaNi0.25 Mn 0.3 Fe 0.2 Ti 0.04 O2.

[0150] (3) Adding layered oxide material A to a ball mill, adding sodium carbonate, nickel oxide, manganese oxide, and aluminum oxide to the ball mill in a molar ratio of 0.74:0.23:0.5:0.08 of metal elements to synthesize a coating layer layered oxide material B. The chemical formula of the coating layer material B is: Na 0.7 Ni 0.23 Mn 0.5 Al 0.08 O2, wherein the molar ratio of the added core layered oxide material A and the coating layer material B is 3:1, acetone is added as a dispersant, and the ball milling is carried out at 200 r / min, the ball milling ratio is 5:1, and after 12 hours of ball milling, it is placed in a vacuum drying oven at 80°C for 2 hours, and the dried material is placed in an alumina crucible in a muffle furnace, and the secondary calcination is adopted, and the temperature is increased to 900°C at 5°C / min for the first calcination. After the heat preservation time is 15 hours, it is naturally cooled to room temperature; then the temperature is increased to 850°C at 5°C / min for the second calcination. After the heat preservation time is 8 hours, it is naturally cooled to room temperature. The atmosphere of the two calcinations is air. After the sintering procedure is completed, the composite layered oxide material Na 0.925 Ni 0.245 Mn 0.35 Fe 0.15 Ti 0.03 Al 0.02 O2. The thickness of the coating layer is 20~80 nm.

[0151] Example 8

[0152] (1) Sodium carbonate, iron oxide, nickel oxide, manganese oxide and lithium carbonate were prepared according to the molar ratio of metal elements of 0.95:0.34:0.35:0.33:0.1, and the materials were placed in the ball mill of a planetary ball mill. Ethanol was added as a dispersant, and the ball milling speed was controlled to 300 r / min. The ball milling ratio was 10:1, and the ball milling was carried out for 6 h. Finally, the obtained material was dried at 80 °C for 12 h to obtain a ball-milled precursor.

[0153] (2) The precursor powder obtained in step (1) is placed in an alumina crucible, and the crucible is placed in a muffle furnace. The crucible is subjected to secondary calcination. The temperature is raised to 900 °C at 5 °C / min, and the first calcination is carried out. The temperature is kept at this temperature for 15 h, and the temperature is naturally cooled to room temperature. Then, the temperature is raised to 850 °C at 5 °C / min, and the second calcination is carried out. The temperature is kept at this temperature for 8 h, and the temperature is naturally cooled to room temperature. The atmosphere for both calcinations is air. After the sintering process is completed, the inner core layered oxide material A is obtained, and its morphology is a round cake, and the particle size is about 3-10 μm. In terms of the amount of metal elements, the chemical formula of the inner core layered oxide material A is: Na 0.9 Ni 0.35 Mn 0.33 Fe 0.34 Li 0.1 O2.

[0154] (3) Adding layered oxide material A to a ball mill, adding sodium carbonate, nickel oxide, manganese oxide, and titanium oxide to the ball mill in a molar ratio of 0.74:0.3:0.4:0.3 of metal elements to synthesize a coating layer layered oxide material B. The chemical formula of the coating layer material B is: Na 0.7 Ni 0.3 Mn 0.4 Ti 0.3 O2, wherein the molar ratio of the added core layered oxide material A and the coating layer material B is 20:1, acetone is added as a dispersant, and the ball milling is carried out at 200 r / min, the ball milling ratio is 5:1, and after 12 hours of ball milling, it is placed in a vacuum drying oven at 80°C for 2 hours, and the dried material is placed in an alumina crucible in a muffle furnace, and the secondary calcination is adopted, and the temperature is increased to 900°C at 5°C / min for the first calcination. After the heat preservation time is 15 hours, it is naturally cooled to room temperature; then the temperature is increased to 850°C at 5°C / min for the second calcination. After the heat preservation time is 8 hours, it is naturally cooled to room temperature. The atmosphere of the two calcinations is air. After the sintering procedure is completed, the composite layered oxide material Na 0.89 Ni 0.348 Mn 0.333 Fe 0.324 Li 0.095 Ti 0.014 O2. The thickness of the coating layer is 20~50 nm.

[0155] Comparative Example 1

[0156] (1) Sodium carbonate, iron oxide, nickel oxide, manganese oxide and zinc oxide were prepared according to the molar ratio of metal elements of 1.05:0.33:0.26:0.33:0.07, and the materials were placed in a ball mill, and ethanol dispersant was added. The ball mill speed was controlled to 300 r / min, the ball mill material ratio was 10:1, and the ball milling time was 6 h. Finally, the obtained material was dried by forced air at 80 °C for 12 h to obtain a ball-milled precursor.

[0157] (2) The precursor powder obtained in step (1) is placed in an alumina crucible, and the crucible is placed in a muffle furnace for calcination. The temperature is raised to 900°C at 5°C / min for the first calcination, and the temperature is kept at this temperature for 15 hours, and the temperature is naturally cooled to room temperature; then, the temperature is raised to 850°C at 5°C / min for the second calcination, and the temperature is kept at this temperature for 8 hours, and the temperature is naturally cooled to room temperature. The atmosphere for both calcinations is air. After the sintering process is completed, a layered oxide with a particle size of about 5 to 10 μm is obtained, which is NaNi 0.26 Mn 0.33 Fe 0.33 Zn 0.07 O2.

[0158] Comparative Example 2

[0159] (1) Sodium carbonate, iron oxide, nickel oxide, manganese oxide and titanium oxide were taken according to the molar ratio of metal elements of 1.05:0.33:0.33:0.28:0.05, and the materials were placed in a ball mill, and ethanol dispersant was added. The ball mill speed was controlled to 300 r / min, the ball mill material ratio was 10:1, and the ball milling time was 6 h. Finally, the obtained material was dried by forced air at 80 ° C for 12 h to obtain a ball-milled precursor.

[0160] (2) The precursor powder obtained in step (1) is placed in an alumina crucible, and the crucible is placed in a muffle furnace for calcination. The temperature is raised to 900°C at 5°C / min for the first calcination, and the temperature is kept at this temperature for 15 hours, and the temperature is naturally cooled to room temperature; then, the temperature is raised to 850°C at 5°C / min for the second calcination, and the temperature is kept at this temperature for 8 hours, and the temperature is naturally cooled to room temperature. The atmosphere for both calcinations is air. After the sintering process is completed, a layered oxide with a particle size of about 1 to 5 μm is obtained, which is NaNi 0.33 Mn 0.28 Fe 0.33 Ti 0.05 O2.

[0161] Application Example 1

[0162] The positive electrode material, conductive agent (acetylene black) and binder (polyvinylidene fluoride) prepared in Examples 1-8 and Comparative Examples 1-2 were mixed in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone was added, stirred and mixed into a slurry, coated on an aluminum foil, vacuum dried for 12 hours, and then pressed into a pole sheet. The prepared composite material was used as the positive electrode, the sodium sheet was used as the negative electrode, the glass fiber was used as the separator, and NaClO4 was used as the electrolyte. A button battery (CR2032) was assembled and the electrochemical performance was tested.

[0163] The electrochemical properties of the materials prepared in Examples 1-8 and Comparative Examples 1-2 were tested by constant current charge and discharge technology at current densities of 2~4.3V, 1C and 2~4.3V, 5C (1C=130 mAh / g) using the Xinwei battery testing system. The test results are shown in Table 2.

[0164]

[0165] Figure 5 The graphs are the cycle performance of the positive electrode materials prepared in Example 1 and Comparative Example 1 tested at 2~4.3V and 5C current density. It can be seen from the graph that at a current density of 5C, the first-round discharge specific capacity of the composite positive electrode material in Example 1 is 88 mAh / g, the discharge specific capacity after 800 cycles is 66.7 mAh / g, and the capacity retention rate is 75.8%; the first-round discharge specific capacity of the positive electrode material in Comparative Example 1 is 77 mAh / g, the discharge specific capacity after 800 cycles is 33 mAh / g, and the capacity retention rate is only 42.9%. Figure 6 The graph is a cycle performance graph of the positive electrode materials prepared in Example 1 and Comparative Example 1 tested at 2~4.3 V and 1C current density. It can be seen from the graph that at a current density of 1C, the capacity retention rate of the composite positive electrode material in Example 1 after 100 cycles is 92.0%; the capacity retention rate of the positive electrode material in Comparative Example 1 after 100 cycles is only 71.0%.

[0166] As can be seen from Table 2, the capacity retention rate of the composite positive electrode material obtained in Example 1-8 after 100 cycles at 1C is 89.4%~93.8%, which is much higher than the capacity retention rate of 71%~75.2% of Comparative Example 1-2. Moreover, the capacity retention rate of the composite positive electrode material obtained in Example 1-8 after 800 cycles at 5C is 71%~77.2%, which is much higher than the capacity retention rate of 42.9%~49.4% of Comparative Example 1-2. The performance of the composite positive electrode material obtained in Example 1-8 in the 1C current cycle test for 100 cycles and the performance in the 5C current cycle test for 800 cycles are both better than those in Comparative Example 1-2, indicating that the P2 / O3 composite layered composite material of the present invention has excellent cycle stability under high voltage and high current conditions.

[0167] Application Example 2

[0168] The layered oxide positive electrode materials prepared in Examples 1-8 and Comparative Examples 1-2 were placed in two high humidity environments for different periods of time to test the air stability of the materials.

[0169] Condition 1: The obtained layered oxide cathode material was stored in an environment with a humidity of 80% and a temperature of 25-29°C for 3 days, then dried at 80°C for 12 h, and then the dried material, conductive agent (acetylene black) and binder (polyvinylidene fluoride) were mixed in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone was added, stirred and mixed into a slurry, coated on aluminum foil and vacuum dried for 12 hours before pressing into a pole piece. The prepared material was used as the cathode, sodium sheet as the cathode, glass fiber as the separator, and NaClO4 as the electrolyte to assemble a button cell (CR2032) and conduct electrochemical performance tests.

[0170] Condition 2: The obtained layered oxide positive electrode material is stored in an environment with an ambient humidity of 40% and a temperature of 25-29°C for 93 days, and then dried at a temperature of 80°C for 12 h. The remaining steps for assembling the button battery are the same as those in condition 1.

[0171] The electrochemical performance of the composite materials prepared in Examples 1-8 and Comparative Examples 1-2 was tested at different humidity levels using a Xinwei battery testing system at a current density of 2-4.3 V and 1 C by constant current charge and discharge technology. The test results are shown in Table 3.

[0172]

[0173] Figure 7 After Example 1 and Comparative Example 1 were placed in an environment with a humidity of 40% for 93 days, the powders were subjected to X-ray diffraction and scanning electron microscopy tests. The X-ray diffraction results showed that the structure of the composite material of Example 1 was almost unchanged, and no peak of impurity sodium carbonate appeared ( Figure 7 (a) in the figure), while the diffraction peak intensity of the material in Comparative Example 1 is significantly reduced, indicating that the crystallinity is significantly reduced, indicating that the material is seriously deteriorated, and a sodium carbonate impurity peak appears ( Figure 7 (b) in the figure). Scanning electron microscopy shows that the crystal surface of Example 1 is smooth, and there is no change in the morphology of the composite material after being placed in air ( Figure 7 The crystal surface of Comparative Example 1 was rough and some particles were broken ( Figure 7 As shown in the illustration of (b) in the figure, before the humidity test treatment, the particles were in the shape of round cakes and had a smooth surface, indicating that the composite layered oxide positive electrode material obtained in the example has excellent air stability.

[0174] Figure 8After the composite materials prepared in Example 1 and Comparative Example 1 were placed in an environment with a humidity of 80% for three days, the cycle performance and rate performance of the materials were tested using the Xinwei battery testing system. It can be seen that the electrochemical properties of the materials did not change in the high humidity environment, indicating that the composite materials have excellent air stability.

[0175] Fig. 9 The SEM image of the planed surface of the composite material particles of Example 1 and the EDS line scan mode test sodium element distribution content data in the particles from left to right. It can be seen from the figure that the distribution of sodium element shows a trend of gradually decreasing from the inside to the outside of the particles when the planed particles are analyzed by EDS, indicating that sodium presents a concentration gradient.

[0176] Fig.10 The SEM image of the planed surface of the composite material particles of Example 1 and the EDS line scan mode test data of the distribution of manganese in the particles from left to right. It can be seen from the figure that the distribution of manganese in the planed particles by EDS element analysis shows a trend of gradually increasing from the inside to the outside of the particles, indicating that manganese is in a concentration gradient.

[0177] Fig.11 for Fig. 9 and Fig.10 Annotated image of composite particles. The circle is a planed particle of the composite material, and the arrow indicates the direction from the outer layer to the inner layer of the composite particle (the length of the arrow does not indicate the thickness of the coating layer).

[0178] Although the above describes the specific implementation methods of the present invention, it does not limit the scope of protection of the present invention. Based on the technical solution of the present invention, various modifications or variations that can be made by those skilled in the art without creative work are still within the scope of protection of the present invention.

Claims

1. A method for preparing a positive electrode material having a gradient structure, characterized in that: The steps include: S1: mixing the raw materials of the core material with the first dispersant, and calcining them twice to obtain the core material; the first calcination temperature is 850-1050°C, and the second calcination temperature is 750-950°C; the first calcination temperature is higher than the second calcination temperature; S2: mixing the raw materials of the core material and the coating layer material with the second dispersant, and calcining them twice to obtain the positive electrode material with the gradient structure; the first calcination temperature is 850-1050°C, and the second calcination temperature is 750-950°C; the first calcination temperature is higher than the second calcination temperature; The positive electrode material is a core-shell structure, which includes a core and a coating layer, wherein the coating layer is coated on the outer surface of the core; the positive electrode material has a composition shown in Formula I: Na e Ni a Mn b Fe c M d O2, wherein 0.89 ≤ e ≤ 1, 0.25 ≤ a ≤ 0.35, 0.28 ≤ b < 0.45, 0.2 ≤ c ≤ 0.4, 0.03 ≤ d ≤ 0.16; the M is selected from one or more of Ti, Mg, Zn, Li, Al, B, Cu, Zr, Y, Ce, La, Sm, Sr, Nb, Ta and V; the concentration of sodium increases from the outer surface to the inner part, and the concentration of manganese decreases from the outer surface to the inner part; The core has a composition shown in Formula II: Na n Ni x Mn y Fe z M 1 k O2, where 0.8≤n≤1.05, 0.25≤x≤0.35, 0.28≤y≤0.33, 0.3≤z≤0.35, 0.04≤k≤0.1; M 1 One or more selected from the group consisting of Ti, Mg, Zn, Li, Cu, Sm and Zr; The coating layer has a composition shown in formula III: Na α Ni β Mn γ M 2 δ O2, where 0.5≤ α≤ 0.7, 0.2≤ β≤0.33, 0.33≤ γ≤ 0.75, 0≤ δ≤ 0.33, M 2 One or more selected from Ti, Mg, Zn, Li, Al, B, Ce, Sr, Ta and Nb; The molar ratio of sodium to all metals except sodium in the core is 0.8-1.3:1; the total molar ratio of sodium to all metals except sodium in the coating layer is 0.5-0.9:1; the core is an O3 type structure, and the coating layer is a P2 type structure; The molar ratio of the coating layer to the core is 1:1.5-3.

2. The method for preparing a positive electrode material having a gradient structure according to claim 1, wherein: In step S1, the raw materials of the core material are mixed with the first dispersant according to a stoichiometric ratio by a solid phase mixing method.

3. The method for preparing a positive electrode material having a gradient structure according to claim 1, wherein: In step S1, the conditions for the first calcination are: a heating rate of 1-5 °C / min, and / or a calcination time of 10-20 h; Furthermore, the conditions for the second calcination are: a heating rate of 1-5 °C / min and a calcination time of 5-10 h; And / or, the atmosphere of the first calcination is an atmosphere containing oxygen; and / or, the atmosphere of the second calcination is one or more of oxygen, air and nitrogen.

4. The method for preparing a positive electrode material having a gradient structure according to claim 1, wherein: In step S2, the core material, the raw materials of the coating layer material in a stoichiometric ratio and the second dispersant are mixed by a solid phase mixing method.

5. The method for preparing a positive electrode material having a gradient structure according to claim 1, wherein: In step S2, the conditions for the first calcination are: a heating rate of 1-5 °C / min, and / or a calcination time of 10-20 h; Furthermore, the conditions for the second calcination are: a heating rate of 1-5 °C / min and a calcination time of 5-10 h; And / or, the atmosphere of the first calcination is an atmosphere containing oxygen; and / or, the atmosphere of the second calcination is one or more of oxygen, air and nitrogen.

6. The method for preparing a positive electrode material having a gradient structure according to claim 1, wherein: The first dispersant is ethanol, acetone or water; And / or, the second dispersant is ethanol, acetone or water.

7. The method for preparing a positive electrode material having a gradient structure according to claim 1, wherein: The molar ratio of the coating layer material to the core material is 1:2-3.

8. A sodium ion battery positive electrode material, characterized in that: The sodium ion battery positive electrode material is prepared by the method for preparing the positive electrode material with a gradient structure according to any one of claims 1 to 7.

9. The sodium ion battery positive electrode material according to claim 8, wherein The particle size of the core is 1-20 μm; And / or, the coating layer has a thickness of 10 to 200 nm.

10. A sodium ion battery positive electrode, characterized in that: The sodium ion battery positive electrode comprises the positive electrode material with a gradient structure as claimed in claim 8 or 9 as a positive electrode active material.

11. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion battery positive electrode according to claim 10, a negative electrode and an electrolyte containing a sodium salt.

12. Application of a sodium ion battery as a power source in photovoltaics, electricity, energy storage systems or mobile storage devices or low-end electric vehicles, characterized in that: The sodium ion battery is the sodium ion battery according to claim 11.

13. An application of a sodium ion battery in distributed energy storage, centralized energy storage or low-end power battery energy storage device, characterized in that: The sodium ion battery is the sodium ion battery according to claim 11.

14. A power system, energy storage system or mobile storage device, characterized in that: It is prepared by the sodium ion battery according to claim 11.

Citation Information

Patent Citations

  • Sodium-ion battery positive electrode material and preparation method and application thereof

    CN114744189A

  • O3 structure layered metal oxide sodium ion battery positive electrode material coated with P2 structure substance and preparation method of O3 structure layered metal oxide sodium ion battery positive electrode material

    CN116435508A

  • Sodium ferric phosphate composite positive electrode material with good conductivity and sodium ion battery

    CN117239095A